Construction and validation of arm wingate test for determination of anaerobic abilities in water polo juniors - Vrdoljak, D.; Kaic, T.; Uljevic, O. (Sports Science and Health, 2022)
The Wingate test is a widely spread test of anaerobic endurance and power in most sports. However, the standard model of the test is based upon a bicycle ergometer for evaluation of lower extremities, therefore, is poorly used in sports that demand a high level of upper body power. This research aims to determine the metric characteristics of the newly constructed arm crank Wingate test. The sample of participants is junior water polo players of VK Mornar Brodospas from Split, Croatia. Mean chronological age is 17-19 years and all participants participated in the test voluntarily. Results are showing a satisfactory level of reliability, homogeneity, and sensibility of measuring instrument and good application in sports such as water polo. Further research should include a bigger sample of participants and athletes from different sports.